Development and Implementation of The Bilingual "Ulos Weaving" Textbook in The Fine Arts Studies Program as Implementation of An Outcomes-Based Curriculum - Daulat Saragi; Osbert Sinaga; Nelson Tarigan (Randwick International of Education and Linguistics Science Journal, 2024)
The aim of research is to develop and apply teaching materials for the Ulos Weaving course in two languages. This is considered important and urgent to address curriculum implementation as per the requirements for ASIIN, ABET and AUN QA accreditation or certification. The problem studied is the validity, effectiveness and practicality of the product being developed. This applied research uses the ADDIE development model developed by Dick and Carry with five stages: analysis, design, development, implementation and evaluation. The objects of product testing were students from the fifth semester fine arts education study program in 1 class (21 people) from 4 classes and 6 lecturers. This research creates innovation and development of teaching materials that are oriented towards textbook products which have an impact on improving the quality of graduates. After the product was validated by 4 experts, material validity was found to be 88% in the very effective category, validation of the layout or appearance of the book was 90%, and validation in Indonesian was 89% and English was 85% in the good category. The results of the student questionnaire were 86.57% and 100% of the lecturers said it was very useful. With the implementation of this textbook, it is hoped that the Ulos Weaving course will become an idol because it is a typical course of the Unimed Fine Arts Department. With this textbook, it will attract the interest of students from other universities and foreign students to study in the FBS Unimed Fine Arts Education Study Program with the Independent Campus Learning Curriculum which is oriented towards results.